The Impact of Corporate Governance and Dividend Policy on Firm Value in Indonesian Non-Financial Firms - Herfiana Astrilia; Iwan Kusmayadi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This research examines the impact of good corporate governance (GCG) and dividend policy on the firm value of non-financial companies listed on the Indonesian Stock Exchange (IDX).Method: The study focuses on 803 non-financial firms listed on the IDX during 2021 to 2023. From this population, a sample of 45 firms was selected using a purposive sampling method. The research utilized secondary data derived from financial statements of the sampled firms and employed panel data regression analysis conducted with EViews 12 software.Result: The findings reveal that institutional ownership significantly and positively affects firm value. Conversely, managerial ownership exerts a significant negative impact on firm value. Meanwhile, the proportion of independent commissioners and dividend policy show a positive but statistically insignificant effect on firm value.Practical Implications for Economic Growth and Development: The study highlights that good corporate governance, particularly institutional ownership, can enhance firm value and potentially driving economic growth by improving market confidence and investment. Additionally, understanding the relationship between dividend policy and firm value can inform better financial strategies that foster long-term stability and growth in non-financial sectors.